2020
DOI: 10.1371/journal.pone.0230041
|View full text |Cite
|
Sign up to set email alerts
|

Unfavorable perceived neighborhood environment associates with less routine healthcare utilization: Data from the Dallas Heart Study

Abstract: Neighborhood environment perception (NEP) has been associated with health outcomes. However, little is known about how NEP relates to routine healthcare utilization. This study investigated the relationship between NEP and independent subfactors with healthcare utilization behavior, as measured by self-reported (1) usual source of healthcare and (2) time since last routine healthcare checkup. We used cross-sectional data from the Dallas Heart Study, which features a diverse, probability-based sample of Dallas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…Hispanic men and women have a lower risk of overall victimization than their Black counterparts, but arguably suffer from more persistent trajectories of violence. The cruel irony is that the health-enabling resources that can mitigate the trauma of repeated and chronic violent victimization – such as counseling and medical care – are in short supply and/or are underutilized in the communities most affected by violence ( Ceasar et al, 2020 , Tung et al, 2018 ). Proactive investment in communities and infrastructure that promotes health to prevent violent crime and victimization may be more productive than merely reacting to the health challenges that often emanate from repeated violence exposure ( Jackson and Vaughn, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Hispanic men and women have a lower risk of overall victimization than their Black counterparts, but arguably suffer from more persistent trajectories of violence. The cruel irony is that the health-enabling resources that can mitigate the trauma of repeated and chronic violent victimization – such as counseling and medical care – are in short supply and/or are underutilized in the communities most affected by violence ( Ceasar et al, 2020 , Tung et al, 2018 ). Proactive investment in communities and infrastructure that promotes health to prevent violent crime and victimization may be more productive than merely reacting to the health challenges that often emanate from repeated violence exposure ( Jackson and Vaughn, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…CACS-based initiation of risk-modifying interventions, for instance by statins, was proven effective for the prevention of AMI at population level, even in low-risk individuals [ 53 , 54 , 55 ]. Individuals from lower socio-economic groups are known to be underrepresented in CAD preventive care and remain unrecognized until suddenly facing AMI or SCD [ 56 ]. To date, it remains unclear if screening the general population by CACS, CRPSs or other tests results in improved clinical outcomes, and, if proven beneficial, whether it would be cost-effective.…”
Section: Screening the General Population For Risk Statusmentioning
confidence: 99%
“…A handful of studies have identified the important role of neighborhood social cohesion in the health of older residents. Specifically, neighborhood social cohesion has been associated with reduced physical symptoms (Robinette et al, 2013) and daily activity limitations (Qin et al, 2021), improved mental health (Elliott et al, 2014), and better routine health care utilization (Ceasar et al, 2020). However, limited studies have examined the impact of neighborhood social cohesion on mobility limitations.…”
Section: Neighborhood Social Cohesion Mobility and Psychosocial Pathw...mentioning
confidence: 99%